The kinematic analysis of female subjects after double-bundle anterior cruciate ligament reconstruction during single-leg squatting - Yamazaki, Junya; Muneta, Takeshi; Ju, Young-Jin; Koga, Hideyuki; Morito, Toshiyuki; Sekiya, Ichiro (Journal of orthopaedic science : official journal of the Japanese Orthopaedic Association, 2013)
The kinematic characteristics of female anterior cruciate ligament (ACL)-injured subjects were recognized in our previous study using an electromagnetic device comparing both female control groups and male ACL-injured subjects during single-leg squatting. To assess the kinematic characteristics of female subjects after double-bundle ACL reconstruction during single-leg squatting. Three-dimensional motion analysis was performed for single-leg squatting in female subjects after ACL reconstruction. We evaluated the relative angles between the pelvis, thigh, and lower leg using an electromagnetic device during single-leg squatting in 28 female subjects with ACL reconstruction. All patients included in this study restored their sports performance level to 90% or higher. Comparing the involved leg to the uninjured leg of female subjects after ACL reconstruction, the involved leg demonstrated significantly more hip adduction and less knee varus than the uninjured leg. Comparing the anterior cruciate ligament-reconstructed female subjects to the healthy female controls, the involved leg after ACL reconstruction demonstrated significantly less hip flexion, more hip external rotation, more hip adduction, and more knee flexion than the dominant leg of the control group. This kinematic study exhibited kinematic characteristics of ACL-reconstructed knees of female subjects. Double-bundle anterior cruciate ligament reconstruction could not quite restore the normal kinematics of female-involved legs compared with both uninjured legs of female subjects and healthy female controls. In future studies, restoring the correct alignment of ACL reconstructed knee during single-leg squatting would be expected to reduce ACL re-injury and to assist a safe return to sport activities.